Oxidized low-density lipoprotein predicts recurrent stroke in patients with minor stroke or TIA. (4th September 2018) - Wang, Anxin; Xu, Jie; Chen, Guojuan; Wang, David; Johnston, S. Claiborne; Meng, Xia; Lin, Jinxi; Li, Hao; Cao, Yibin; Zhang, Nan; Ma, Caiyun; Dai, Liye; et al.
Abstract : Objective: To investigate the association between oxidized low-density lipoprotein (oxLDL) and recurrent stroke in patients with minor stroke or TIA. Methods: In the Clopidogrel in High-Risk Patients With Acute Nondisabling Cerebrovascular Events (CHANCE) trial, baseline oxLDL levels were blindly measured in plasma with the 4E6 antibody in the core laboratory. The primary outcome was any stroke within 90 days. The secondary outcomes included any stroke within 1 year and ischemic stroke and combined vascular events within 90 days and 1 year. The associations of oxLDL with recurrent stroke were analyzed by Cox proportional hazards. Results: Among 3, 019 patients included in this study, the median (interquartile range) of oxLDL was 13.96 (6.65–28.81) μg/dL. After adjustment for conventional confounding factors, patients in the highest oxLDL quartile (≥28.81 μg/dL) had a higher risk of recurrent stroke within 90 days (hazard ratio 1.43, 95% confidence interval 1.03–1.98) compared to those in the lowest oxLDL quartile (<6.65 μg/dL). Similar results were found for secondary outcomes. We also found a J-shaped association between oxLDL and risk of each outcome. There were no significant interactions between oxLDL and low-density lipoprotein and use of dual antiplatelet, antihypertensive, antidiabetic, and statins agents. Conclusions: Elevated oxLDL levels can independently predict recurrent stroke in patients with minor stroke or TIA. ClinicalTrials.gov identifier: NCT00979589.